AN INVESTIGATION OF PARENTAL FACTOR AS A DETERMINANT OF CHILD TRANSITION READINESS FROM PRE - SCH OOL TO PRIMARY SCHOOL IN RUIRU, KIAMBU COUNTY KENYA - Gitahi, Magdalene W.; Kamau, M. Joyce; Mwaura, William W.; Thinguri, Ruth; Koech, Peter (Academic Research International, 2017)
It is undisputable fact that parents are the primary care givers of their children. The gist of the study was to investigate parents as determinant of children readiness transisting from pre-school to primary one in Ruiru sub- county, Kiambu County in Kenya. The results should assist parents and the government in realizing the importance of successful transition and especially from pre-school to primary one. The study employed mixed methodology in data collection and analysis. Both quantitative and qualitative data were collected concurrently. To ensure all the identified sub-groups in the target population were well represented, the study applied stratified sampling and simple random sampling. Questionnaires and interviews were used to collect the data. Pilot study was carried out to test the reliability of the instruments. Through the appraisal and guidance of the experts in the early childhood department, Mount Kenya University, the validity of the instruments was established. The quantitative data was analyzed with the use of tables, frequencies and a percentage while qualitative data collected was thematically analyzed. The study found out that transition of some children and especially from pre-school to primary one is a challenge. The researchers concluded that parents have a great role in relation to influencing the transition of their preschoolers joining primary school. However inadequate resources undermine parent’s ability to provide for their children adequately. The study recommends that the government should socially and economically empower the parents and also include the early childhood programmes in the free education.
Keywords: Parental factor; Readiness; Transition; Pre-schoolers; Holistic development; Single parenthood